University-industry collaborations and its impact on firm performance - Imaduddin, Abidin (2022)
SMEs in Malaysia share a very worrying situation. The SME Master Plan 2012 to 2020 states that 42% of SMEs that started business in 2000 failed to continue their business in 2005. It is believed that one of the solutions to this problem is collaboration between SMEs and universities. The purpose of this research is to provide an improved understanding of how university-industry collaborations (UIC) are measured and how they can give impact to the issues of graduate competency, knowledge transfer, technology transfer, and innovation on firms’ competitive advantage and performance. This research will discuss Resource-Based View (RBV) as a main theory. This research is mainly a quantitative study that consists of descriptive analysis and Confirmatory Factor Analysis (CFA) followed by Partial Least Square approach to Structural Equation Modelling (SEM) procedure to answer the research questions. 151 firms had responded to the survey. Overall, two (2) UIC dimensions which are graduate competency, and innovation are supporting firm competitive advantage as well as firm performance whereas another two (2) dimensions are not supporting which are knowledge transfer, and technology transfer. The structure model of this study gives an understanding that there are still variables out there that can help explain the role of UIC to SME firm performance. In addition, considering the unit of analysis of this study that puts SMEs, researchers also are recommended to take large companies as a unit of analysis in future studies and it is expected that the conceptual model will change. This model can also be used to view UIC's impact on universities or academics instead of impact on firms. Additionally, impact towards firm may be moderated by any other variables that are possible such as university classification, level of development of a country and company size.